FROM ROTE MEMORIZATION TO NEURAL INTEGRATION: THE EVOLUTION OF LANGUAGE ACQUISITION ACROSS THE XX AND XXI CENTURIES - Khalilov Bakhodir Tolibovich (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Thesis: “The transition of language acquisition from the XX to the XXI century represents a fundamental shift from prescriptive linguistics—focused on structural accuracy and rote repetition—to connective and neuro-adaptive fluency. In the current era, the learner’s role has evolved from a passive recipient of grammatical rules to an active navigator of a hybrid digital-biological ecosystem, where success is measured not by lexical retention, but by the ability to synergize human cultural pragmatics with ubiquitous generative artificial intelligence.”